Chemical Synthesis of Homogeneous Glycoproteins for the Study of Glycoprotein Quality Control System. Issue 3 (20th February 2015) - Izumi, Masayuki; Dedola, Simone; Ito, Yukishige; Kajihara, Yasuhiro
Abstract: The glycoprotein quality control system exists in the endoplasmic reticulum to maintain protein homeostasis and prevent accumulation of aberrant glycoproteins. Folding sensor enzyme uridine diphosphate (UDP)glucose : glycoprotein glucosyltransferase (UGGT) plays an important role in this system through its ability to discriminate immature or misfolded glycoproteins from native ones. UGGT transfers a glucose residue to a glycoprotein containing Man9 GlcNAc2 (M9; Man=mannose, GlcNAc= N ‐acetyl‐D ‐glucosamine) N ‐glycan only when the glycoprotein has not attained a native form. We chemically prepared homogeneous glycoproteins containing M9 N ‐glycan in the native form as well as in misfolded forms and examined them as substrates of UGGT. Glucose transfer to misfolded glycoproteins was clearly observed by LC‐MS, but glycoproteins in the native form were barely glucosylated. Furthermore, we constructed an in vitro glycoprotein folding system in the presence of UGGT and found out that all folding intermediates which appeared during folding were also glucosylated. Through these experiments, we demonstrated the usefulness of chemically synthesized homogeneous glycoproteins as probes to gain insights into the molecular basis of the glycoprotein quality control system. Abstract :